Albuminuria in Association with Cognitive Function and Dementia: A Systematic Review and Meta-Analysis - Georgakis, Marios K; Dimitriou, Nikolaos G; Karalexi, Maria A; Mihas, Constantinos; Nasothimiou, Efthimia G; Tousoulis, Dimitrios; Tsivgoulis, Georgios; Petridou, Eleni Th (Journal of the American Geriatrics Society, 2017)
OBJECTIVES: Cerebral microvascular disease is considered to contribute to cognitive dysfunction. We opted to explore whether albuminuria, a marker of systemic microangiopathy, is associated with cognitive impairment, dementia, and cognitive function. DESIGN: Systematic review; independent reviewers screened 2359 articles, derived through the search strategy, for identification of observational studies quantifying an association of albuminuria with the outcomes of interest, abstracted data on study characteristics and results and evaluated studies on quality using the Newcastle-Ottawa scale. SETTING: Community. PARTICIPANTS: Adults. MESUREMENTS: Cognitive impairment and dementia, defined by validated neuropsychological tests or clinical guidelines, respectively, and cognitive function, assessed by validated instruments. RESULTS: Thirty-two eligible studies were identified. Albuminuria was associated with cognitive impairment (Odds Ratio (OR): 1.35, 95% Confidence Interval (CI): 1.19-1.53; 7,852 cases), dementia (OR: 1.35, 95% CI: 1.10-1.65; 5,758 cases), clinical Alzheimer's disease (OR: 1.37, 95% CI: 1.11-1.69; 629 cases) and vascular dementia (OR: 1.96, 95% CI: 1.16-3.31; 186 cases); the effect remained significant among longitudinal, population-based and high quality studies. Time-to-event analysis on prospective studies of non-demented at baseline individuals also showed a significant association with incident dementia (Risk Ratio: 1.52, 95% CI: 1.16-1.99; 971 cases). Worse global cognitive performance (Hedge's g: -0.13, 95% CI: -0.18, -0.09; 68,348 subjects) and accelerated cognitive decline (g: -0.20, 95% CI: -0.34, -0.07; 31,792 subjects) were noted among subjects with albuminuria, who also scored lower in executive function, processing speed, verbal fluency, and verbal memory. CONCLUSIONS: Albuminuria was independently associated with cognitive impairment, dementia and cognitive decline. The stronger effects for vascular dementia and cognitive performance in domains primarily affected by microvascular disease support that the association could be mediated by shared microvascular pathology in the kidney and the brain.
Keywords: dementia; Humans; neuropsychologické testy; demence; cognitive impairment; nemoci cév; kognice; Albuminuria; lidé; microvascular disease; Vascular Diseases; albuminurie; Neuropsychological Tests; albuminuria; Cognitive Dysfunction; Dementia; Cognition; kidney disease; kognitivní dysfunkce